2005
DOI: 10.1063/1.1867355
|View full text |Cite
|
Sign up to set email alerts
|

Effective conjugation and Raman intensities in oligo(para-phenylene)s: A microscopic view from first-principles calculations

Abstract: Electron-phonon coupling in oligo(para-phenylene)s is addressed in terms of the off-resonance Raman intensities of two distinct modes at 1220 and 1280 cm(-1). On the basis of Albrecht's theory, vibrational coupling and Raman intensities are calculated from first-principles quantum-chemical methods. A few-state model is used to evaluate the dependence of the mode intensities on oligomer length, planarity, and excitation wavelength. The link between electron delocalizationconjugation and Raman intensities is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 77 publications
(100 reference statements)
4
51
0
Order By: Relevance
“…This also shows that the 1220 cm 1 mode, which is associated with the delocalized orbitals, is more strongly pre-resonance enhanced than the 1280 cm 1 mode as the exciting laser approaches resonance with the lower energy delocalized band. 37 In Fig. 4(b), we show the ratio of the intensities of the 1220 cm 1 mode and 1280 cm 1 mode for POPs containing between three and six repeat units as a function of the laser wavelength.…”
Section: CM −1 Mode and 1280 Cm −1 Modementioning
confidence: 99%
See 4 more Smart Citations
“…This also shows that the 1220 cm 1 mode, which is associated with the delocalized orbitals, is more strongly pre-resonance enhanced than the 1280 cm 1 mode as the exciting laser approaches resonance with the lower energy delocalized band. 37 In Fig. 4(b), we show the ratio of the intensities of the 1220 cm 1 mode and 1280 cm 1 mode for POPs containing between three and six repeat units as a function of the laser wavelength.…”
Section: CM −1 Mode and 1280 Cm −1 Modementioning
confidence: 99%
“…[33][34][35] The ratio of the intensities of these two peaks is also an indicator of the inter-ring torsion angle. [36][37][38][39] In PPP materials, all the molecular orbitals can be divided into delocalized orbitals and localized orbitals. Theoretical calculations 37,44 further showed that the delocalized orbitals are mainly associated with the C atoms on the long molecular axis and strongly sensitive to the conjugation (chain length and planarity), whereas the localized orbitals are mainly contributed by the off-axis C atoms and are far less susceptible to conjugation effects.…”
Section: CM −1 Mode and 1280 Cm −1 Modementioning
confidence: 99%
See 3 more Smart Citations